Peroxisomal PEX7 Receptor Affects Cadmium-Induced ROS and Auxin Homeostasis in Arabidopsis Root System - Diego Piacentini; Federica Della Rovere; Ilaria Bertoldi; Lorenzo Massimi; Adriano Sofo; Maria Maddalena Altamura; Giuseppina Falasca (MDPI AG, 2021)
Peroxisomes are important in plant physiological functions and stress responses. Through the production of reactive oxygen and nitrogen species (ROS and RNS), and antioxidant defense enzymes, peroxisomes control cellular redox homeostasis. Peroxin (PEX) proteins, such as PEX7 and PEX5, recognize peroxisome targeting signals (PTS1/PTS2) important for transporting proteins from cytosol to peroxisomal matrix. pex7-1 mutant displays reduced PTS2 protein import and altered peroxisomal metabolism. In this research we analyzed the role of PEX7 in the Arabidopsis thaliana root system exposed to 30 or 60 μM CdSO4. Cd uptake and translocation, indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA) levels, and reactive oxygen species (ROS) and reactive nitrogen species (RNS) levels and catalase activity were analyzed in pex7-1 mutant primary and lateral roots in comparison with the wild type (wt). The peroxisomal defect due to PEX7 mutation did not reduce Cd-uptake but reduced its translocation to the shoot and the root cell peroxisomal signal detected by 8-(4-Nitrophenyl) Bodipy (N-BODIPY) probe. The trend of nitric oxide (NO) and peroxynitrite in pex7-1 roots, exposed/not exposed to Cd, was as in wt, with the higher Cd-concentration inducing higher levels of these RNS. By contrast, PEX7 mutation caused changes in Cd-induced hydrogen peroxide (H2O2) and superoxide anion (O2●−) levels in the roots, delaying ROS-scavenging. Results show that PEX7 is involved in counteracting Cd toxicity in Arabidopsis root system by controlling ROS metabolism and affecting auxin levels. These results add further information to the important role of peroxisomes in plant responses to Cd.